Biodanza for kindergarten children (TANZPRO-Biodanza): reporting on changes of cortisol levels and emotion recognition. Issue 1 (2nd January 2016) - Stueck, Marcus; Villegas, Alejandra; Lahn, Franziska; Bauer, Katrin; Tofts, Paul; Sack, Ulrich
Abstract: The evidence-based programme "TANZPRO-Biodanza for children" was developed in 2009 by Marcus Stueck and Alejandra Villegas based on the Biodanza concept of Rolando Toro and Cecilia Luzzi (Children-Biodanza). The 10-session programme includes elements of dance, movement, encounter and non-verbal communication. There are two versions of the programme, for younger children aged 4–6, and older children, aged 7–12. TANZPRO-Biodanza is the nonverbal part of the School of Empathy concept, based on an integrative empathy model by Stueck (2013b, verbal part: "Respectful, nonviolent communication"). In the current study (10 children, age 4–6), a significant reduction in cortisol and improvements in emotion recognition and concentration (in children with high or medium pre-cortisol values) were found. This indicates the potential of TANZPRO-Biodanza to promote stress reduction and the enhancement of social skills. Despite the methodical limitations, the current study is a valid pilot and gives a first insight into the effects of dance on the responses and modulation of neurohormones in 4–6-year-old children.